Effects of Flaxseed on Blood Pressure in Patients Taking Antihypertensive Drugs: A Randomized Trial - Verma, Rakesh; Singh, Bivek; Rauniyar, Gajendra Prasad; Koirala, Bhawesh; Sharma, Sanjib Kumar; Chapagain, Utshav; Singh, Abhishek; Verma, Rupesh; Karna, Pooja (Nepalese Heart Journal, 2024)
Background The cardiovascular protective effects of consuming flaxseed, such as improving lipid profile and reducing inflammatory markers, have been studied in both animals and humans. This study aimed to assess the effects of flaxseed in patients taking antihypertensives and compare their blood pressure before and after daily consumption of flaxseed on days 0, 45, and 90. Methods This randomized trial was registered at ClinicalTrials.gov (Identifier: NCT0475950). A single-blind, parallel-group, prospective interventional randomized clinical trial was conducted using a lottery sampling method. Systemic blood pressure measurements were taken on days 0, 45, and 90. Descriptive statistics, including percentages, means, and standard deviations (SD), were calculated and presented. Inferential analyses involved independent t-tests and paired t-tests. Results Out of 72 hypertensive patients, 34 were males and 38 were females. No patients withdrew from the study after final enrollment. The mean age of enrolled patients was 55.38 years, and the mean BMI was 26.53 kg/m2. After 90 days, the flaxseed group demonstrated a significant reduction in mean Systolic Blood Pressure (SBP) from 151.62 to 131.89 mmHg, equating to a 13.01% decrease versus 4.77 % reduction in placebo group (p-value = 0.001). While there was also a reduction in mean Diastolic Blood Pressure (DBP) from 94.86 to 81.08 mmHg, corresponding to a 14.53% decrease in flaxseed group versus 5.7% reduction in placebo group, this change was not statistically significant (p-value = 0.082). Conclusion Flaxseed, when given alongside antihypertensives to patients with hypertension, can be effective and safe in maintaining blood pressure, thus reducing the risk of cardiovascular diseases.